Amoxicillin and Ceftriaxone as Treatment Alternatives to Penicillin for Maternal Syphilis - Yuichi Katanami; Takehiro Hashimoto; Saho Takaya; Kei Yamamoto; Satoshi Kutsuna; Nozomi Takeshita; Kayoko Hayakawa; Shuzo Kanagawa; Norio Ohmagari (Emerging Infectious Diseases, 2017)
There is no proven alternative to penicillin for treatment of maternal syphilis. We report 2 case-patients with maternal syphilis who were successfully treated without penicillin. We used amoxicillin and probenecid for the first case-patient and amoxicillin, probenecid, and ceftriaxone for the second case-patient.